Quantifying consumptive water footprints of soybean in rainfed and irrigated systems under climate change scenarios - Barrera, Wilfredo; Morbidini, Francesco; Maucieri, Carmelo; Giordano, Maria; Pogačar, Tjaša; Flajšman, Marko; Ghinassi, Graziano; Verdi, Leonardo; Ferrise, Roberto; Dalla Marta, Anna (Frontiers in Agronomy, 2026)
IntroductionUnderstanding climate change impacts on water footprints (WFs) is crucial for sustainable soybean production.MethodsWe utilized previously calibrated AquaCrop model to assess baseline (1981–2010) and future climate change impacts on soybean WFs under Shared Socio-economic Pathways (SSPs) emission scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in rainfed and irrigated systems.ResultsThe WFrainfed varied across locations in the baseline period, with Cesa having the highest values and Ljubljana the lowest. Blue WF and WFirrigated increased as the readily available water (RAW) depletion threshold for irrigation decreased, with no significant differences in WFirrigated across irrigation strategies. Future climate change showed varying effects on WFrainfed and WFirrigated. Under SSP1-2.6 and SSP5- 8.5, WFrainfed is projected to increase from mid (2061–2080) to far future (2081– 2100). Whereas, a decrease is projected from near (2041–2060) to far future under SSP2-4.5. WFirrigated is expected to decrease in Castelfranco and Cesa but to increase in Ljubljana. Under SSP5-8.5, WFirrigated increased from near to far future. Whereas, SSP2-4.5 showed a decline, except in Ljubljana from near to mid-future. Under SSP1-2.6, WFirrigated decreased from near to mid-future but increased from mid to far future. Blue WF followed similar patterns to these projections. Irrigation strategies have minimal effects on consumptive WFs but significantly influence blue water use and yield.DiscussionFuture climate change will differentially impact rainfed and irrigated soybean WFs, emphasizing the need for targeted irrigation water management strategies. The findings are essential to making informed decisions for sustainable soybean production in the study areas.